TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAME WORK COBIT 4-1 DENGAN MODEL MATURITY LEVEL PERUSAHAAN TELEKOMUNIKASI - Chandra, Adityawan (Jurnal Teknologi Technoscientia, 2017)
Information technology significantly affects and determines the management of the company. A framework is needed to ensure that information technology enables companies to maximize profits, Information technology risk management and information technology resources are used efficiently. Evaluation of information technology is needed to better ensure the achievement of business goals. PT. Telkom Witel Yogyakarta a company engaged in the field of telecommunications has been using information technology to support the smooth operation of the company. Assessment of maturity level using COBIT 4-1 framework on information technology governance Telkom Witel Yogyakarta needs to be evaluated, so recommendations for improvement and improvement of information technology governance can be delivered. Research with survey method using questionnaire based on COBIT framework 4.1. Questionnaire of six answer choices from 25 respondents for Deliver and Support (DS) domain and four domains Monitor and Evaluate (ME). SPSS 16 for Windows software is used to process maturity level data. 12 domains are below the expected value: DS.1 (0.79), DS. 4 (0.76), DS.6 (0.19), DS.7 (0.83), DS.9 (0.80), DS.10 (0.13), DS.11 (0.59), DS. 13 (1.11), ME.1 (0.09), ME.2 (0.09), ME.3 (0.76) and ME.4 (1.17). Five domains that have values above expected maturity values: DS.2: 3.00, DS.3: 3.96, DS.5: 3.50, DS.8: 3.96 and DS.12: 3.05. Maturity level of information technology governance in Witel Yogyakarta DS domain and ME domain of 10 information systems with average maturity: 3.17 (defined process). The expected maturity value varies for each domian with a range between the 3.00 level and the 4.00 level. The highest maturity value of the DS domain is DS.3 and DS.8 value: 3.98, the lowest value DS.6: value 2.81. The highest maturity value of the ME domain is ME.3 with a value of 3.24, the lowest value of ME.4 with a value of 2.83.